Vowel Phonotactics in Modern Korean Phonology: A Corpus-Based Approach - Tae-Jin Yoon (Languages, 2023)
Ideophones are believed to exhibit distinct phonotactic patterns compared to regular language, in their expressiveness. Vowel harmony can be observed in ideophones in Modern Korean. However, over time, Korean has gradually lost its regular vowel harmony process, due to the influx of foreign words, especially from Chinese, and historical sound changes like the vowel shift of /ɔ/ to different vowel types. Previous studies have mainly focused on the vowel patterns of ideophones without necessarily comparing the degree of vowel harmony between ideophones and other lexical strata. This lack of comparison makes it challenging to assess the level of corruption in vowel harmony specifically within ideophones, relative to other components of the lexicon. To address this gap, this paper examines vowel patterns extracted from the online dictionary of Korean, developed by the National Institute of the Korean Language (NIKL) with contributions from anonymous users and specialists. The analysis specifically explores vowel patterns across lexical items with varying syllable lengths, focusing on the lexical stratum, adverbial parts of speech, and the semantic meaning of the adverbials. This examination aims to assess the regularity of vowel sequencing and determine the extent of purity in vowel harmony patterns. The quantitative analysis of the compiled dictionary provides valuable insights into the degree of irregular phonotactics and its relationship to sound symbolism in Modern Korean.